Ischemic modified albumin as a new biomarker in predicting oxidative stress in alopecia areata - ATAŞ, Hatice (Turk J Med Sci, 2019)
BACKGROUND/AIM: Results show that oxidative stress is a pathophysiologic factor for alopecia areata (AA); however, the markers used can be confounding. Thus, we aimed to investigate the role of oxidative stress in the pathogenesis of AA through an evaluation of ischemia-modified albumin (IMA); other markers of the oxidant/antioxidant system, such as SOD, CAT, GSH-ST, and MDA; and contributing clinical risk factors. MATERIALS AND METHODS: The usefulness of IMA as a new marker for oxidative stress was compared with that of other markers and evaluated in patients with AA. RESULTS: The mean serum level of IMA was of higher statistical significance in AA patients than in the control group (IMA: 0.57 ± 0.01 vs. 0.52 ± 0.02 ΔABSU, P < 0.0001). IMA (P = 0.03, OR = 25.8, 95% CI = 1.4–482.7) was found to be an independent predictor of oxidative stress in patients with AA. Increased severity of AA was found as an independent risk factor for IMA. CONCLUSION: Long-lasting disease, male sex, >1 site of involvement of disease, and increased severity of disease were correlated with increased oxidation. Presence of AA, male sex, and severe disease were determined to be independent risk factors for antioxidant and oxidant systems. IMA has great potential as a biomarker of oxidative stress in AA when compared to other studied biomarkers.